Characterisation of the lymphoid stress surveillance response in human intestine. (25th February 2016) - Dart, Robin; Woolf, Richard; Irving, Peter; Hayday, Adrian
Abstract: Background: The human intestine harbours an immense repertoire of T cells, many having proved difficult to isolate and characterise. The lymphoid stress surveillance response (LSSR), whereby unconventional T cells respond to epithelial dysregulation in synchrony with innate myeloid cells, was first described in mice. We investigated the potential for LSSR in human intestine, and whether this response could contribute to gut inflammation. Methods: We obtained colonic biopsy samples at endoscopy from healthy donors. We applied a novel explant culture system (from one described in human skin) that permits outgrowth of large numbers of highly viable T cells, to complete flow-cytometric phenotyping and functional studies. To validate our method we compared T cell isolation methods. Findings: Validation of our method demonstrated that cell yield was twice as high as with conventionally isolated cells. γδ T cells comprised a substantial, underappreciated proportion of total intestinal lymphocytes (mean 9·5%, SD 9). Gut γδ T cells expressed a tissue-resident memory phenotype, including the activating receptor NKG2D. As previously demonstrated by us in human skin, specific cytokines licensed such cells to make purely innate-like cytotoxic responses, both to recombinant NKG2D ligands and to colonic tumour cell lines. Responses to colonic tumour cell lines were abrogated by antibodies that block NKG2D, demonstrating common functional potentials at distinct epithelial surfaces. Interpretation: The study shows that the human intestine harbours a large number of tissue-resident γδ T cells that can make rapid, innate-like responses to epithelial cell dysregulation, akin to those shown in our laboratory both in vivo for their mouse counterparts, and in skin. We can now investigate the contribution of LSSR to inflammatory gastrointestinal diseases characterised by tissue dysregulation and the upregulation of stress ligands. Funding: Francis-Crick Institute - National Institute for Health Research Biomedical Research Centre (Clinical Research Training Fellowship), Wellcome Trust.